2016
DOI: 10.1002/eji.201545939
|View full text |Cite
|
Sign up to set email alerts
|

IL‐12 and IL‐4 activate a CD39‐dependent intrinsic peripheral tolerance mechanism in CD8+ T cells

Abstract: Immune responses to protein antigens involve CD4+ and CD8+ T cells, which follow distinct programs of differentiation. Naïve CD8 T cells rapidly develop cytotoxic T‐cell (CTL) activity after T‐cell receptor stimulation, and we have previously shown that this is accompanied by suppressive activity in the presence of specific cytokines, i.e. IL‐12 and IL‐4. Cytokine‐induced CD8+ regulatory T (Treg) cells are one of several Treg‐cell phenotypes and are Foxp3− IL‐10+ with contact‐dependent suppressive capacity. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…It should be borne in mind that, in the various existing studies, CD8+ T cells were retrieved and characterized using different methodological approaches in terms of patient groups or murine models, biological samples, and study methods. These aspects may account for most of the discrepancies observed, which have indeed been clustering around a non-relevant role (4), a protective role (5), or a disease-favoring role, including association with poorer lung function (610) and possibly involving a significant direct and indirect contribution toward a Th2-high bronchial inflammation (11, 12). Nevertheless, it should also considered that different conditions of the local milieu in the target organ, possibly involving exposure to different cytokines and/or antigen-producing cells may also explain discrepant results across existing studies.…”
Section: General Aspects About the Role Of Cd8+ T Cells In Human Asthmamentioning
confidence: 99%
See 2 more Smart Citations
“…It should be borne in mind that, in the various existing studies, CD8+ T cells were retrieved and characterized using different methodological approaches in terms of patient groups or murine models, biological samples, and study methods. These aspects may account for most of the discrepancies observed, which have indeed been clustering around a non-relevant role (4), a protective role (5), or a disease-favoring role, including association with poorer lung function (610) and possibly involving a significant direct and indirect contribution toward a Th2-high bronchial inflammation (11, 12). Nevertheless, it should also considered that different conditions of the local milieu in the target organ, possibly involving exposure to different cytokines and/or antigen-producing cells may also explain discrepant results across existing studies.…”
Section: General Aspects About the Role Of Cd8+ T Cells In Human Asthmamentioning
confidence: 99%
“…Another study, involving asthmatic patients who were followed up for 14 years showed that the decline in lung function (FEV 1 ), although mild, was clearly correlated with the number of CD8+ T-cells in airway biopsies, not just at baseline but also on follow-up (5). Curiously, a recent study in asthmatic patients demonstrated that the degree of airflow obstruction (FEV 1 and FEF 25–75 ) was correlated not with the total number of CD8+ T cells but rather with the number of CD8+ T-cells in the bronchoalveolar lavage fluid which expressed the high-affinity receptor for leukotriene B4 (BLT1) and produced IL-13 (10).…”
Section: General Aspects About the Role Of Human Nk-like Cd8+ T Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asthma has been traditionally associated with an expansion of CD4 + type 2 helper T (Th)-cells in response to allergen exposure and these cells are considered mainly responsible for the disease. Thus, it is not surprising that a correlation between CD4 [11][12][13][14][15][16]. But which subset, or subsets are found in asthma?…”
Section: Second: the Possible Role Of Cd8 + T-cells In Asthmamentioning
confidence: 99%
“…Interestingly, it has been shown that CD8 + T-cells can develop this Foxp3-independent suppressive activity only in the absence of alarmins [16]. Thus, this mode of action would promote peripheral tolerance to immunogenic antigens that do not cause tissue damage.…”
Section: Foxp3mentioning
confidence: 99%